Study of temporal variations of nocturnal and daytime urban heat island in Baghdad - Naif, Salwa S.; Hadi, Najlaa M.; Al-Jiboor, Monim H. (Scientific Review Engineering and Environmental Sciences (SREES), 2020)
Based on daily minimum and maximum air temperature observations for three years: 2008, 2013 and 2019, measured by automatic weather stations located at two sites of Baghdad city were used to compute nocturnal and daytime urban heat island (UHI). First station fixed in campus of the Mustansiriyah University is considered as urban area, and another station followed to Iraqi meteorological organization installed at the International Baghdad Airport was chosen as the rural site. Daily, seasonal and annual averages of nocturnal and daytime UHIs were presented to study the variability and trends. The results show the evolution of a nocturnal UHI, whose high mean values were recorded in four seasons with largest value found in summer of 2019. Annual trend in nocturnal UHI intensities was found to be larger than that of daytime. Thus, this study propose that maintenance and increase urban parks and planting shading tall trees to mitigate UHI intensity in Baghdad city.